PENINGKATAN KESEJAHTERAAN KELUARGA DAN PENDAMPING ANAK BERKEBUTUHAN KHSUSUS MELALUI PELATIHAN PEMBUATAN SABUN DAN LILIN AROMATERAPI DARI MINYAK JELANTAH - Kurniati Zainuddin; Haerani Nur; Eka Sufartianingsih Jafar; Asniar Khumas; Rohmah Rifani (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2023)
Skills training should be provided according to individual abilities and interests. So that individuals with special needs can develop their ability to be independent at an optimal stage. The purpose of this program is to develop families with individuals with special needs. In order to provide social support and skills to individuals with special needs to optimize their abilities. This program helps improve the skills of individuals with special needs to create works with materials that are easy to find. This program is divided into three stages, namely preparation, implementation, and evaluation starting from preparing teaching media in the form of cards and other materials, implementing activities for 1 day with a learning menu, namely making soap and candles from used cooking oil waste. The implementation of PKM is carried out at the location of Sentra Wirajaya partners. Evaluation of training results is carried out by conducting observations and interviews with several training participants.  The results show that parents find it helpful to get material that is easy to teach to children and can be an activity of economic value for children with special needs.